Increasing Community Preparedness In Facing Floods Disaster In Jakarta City - Muliandi Madjid, Mohd; Bangun, Ernalem; Juni Risma, Herlina; Wilopo, Wilopo (CV. AFDIFAL MAJU BERKAH, 2024)
Flood disasters are the third cause of economic loss of all natural disasters throughout the world. Jakarta, as a waterfront city, is often hit by floods every year, especially during the rainy season. This research is focused on identifying and analyzing community responses and their relationship with their knowledge, preparedness and level of action towards disasters. This research is an exploratory case study research based on primary and secondary data. Research findings show that people in coastal areas have a high level of knowledge about floods (64%). This knowledge is high relative to the sum of their past experiences; However, they are less prepared (43%) because most of the residents are fishermen with low incomes so they don't have to make much effort to adapt to flood-affected houses. On the other hand, people in the interior, they lack knowledge (18%), but they have a good level of preparedness (24%) because of their relatively high-income level. Furthermore, both communities in coastal and inland areas had a high level of action due to high levels of knowledge and experience for coastal residents and good preparedness for inland residents.